Development of a novel affinity maturation strategy utilizing error-prone PCR and mammalian display - Lankinen, Elisa (My University, 2025)
In vitro affinity maturation is a strategy for improving antibody affinity through an iterative process of diversification and selection. Error-prone PCR (epPCR) can be used to artificially introduce random mutations into the antibody gene, mimicking the natural somatic hypermutation process. Diverse antibody libraries are displayed on the surface of mammalian cells by linking the antibody phenotype to genotype utilizing mammalian display. Mammalian display enables screening and selection of full-length IgG antibodies for developability properties. The aim of this study was to determine whether the developability properties of an antibody can be improved using epPCR combined with mammalian display. Fab 002OH A05 was converted into IgG, and its variable domains were subjected to random mutagenesis using epPCR to generate separate antibody maturation libraries for the variable light and heavy domains. The selection was performed using the mammalian display platform. First, the cells displaying the antibody were enriched using magnetic-activated cell sorting, followed by fluorescence-activated cell sorting, where the cells were sorted into subpopulations based on their expression levels and antigen binding levels. A total of 9 variants and parental antibody were transiently expressed and purified to evaluate biophysical properties and affinity. Libraries from different selection stages were retrospectively analyzed using next-generation sequencing to determine the quality of the libraries and what types of mutations were enriched. Variants with biophysically favorable aggregation levels, melting temperatures, hydrophobicity, and polyreactivity were identified. Self-association was reduced in all variants, but along with heterogeneity, it requires further engineering. Antibody affinity was improved for three variants, although the increase was only twofold for the most improved variant as measured by surface plasmon resonance. However, the reformatted parental 002OH A05 IgG had already significantly higher affinity than previously measured as a Fab using biolayer interferometry. Still, all variants retained excellent affinities in the sub-nanomolar range. Based on the next-generation sequencing, some variants were enriched up to 16.2-fold and 15.0-fold in the variable light and heavy libraries, respectively, and all the most enriched variants showed only single amino acid mutations in both framework and complementarity-determining regions. Mutational hotspots were identified in the enriched variants of both libraries. The applied strategy is promising and this study demonstrates how a wide range of mutations may be required for successful in vitro affinity maturation.
Keywords: affinity maturation, antibody engineering, biophysical characterization, error-prone PCR, gelsolin amyloidosis, mammalian display